The Ruby on Rails tutorial LiveLessons (sneak peak video trainign) : learn web development with Rails - Hartl, Michael; Safari eBooks ([Place of publication not identified] : Addison-Wesley Professional, 2015)
"Best-selling author and leading Rails developer Michael Hartl teaches Rails by guiding you through the development of three example applications of increasing sophistication, focusing on the fundamental techniques in web development needed for virtually any kind of application. The updates to this edition include simplified installation via a standard integrated development (IDE) in the cloud, use of the default Rails stack throughout, a light-weight testing approach, an all-new section on image upload, and an all-new chapter on account activation and password resets, including sending email with Rails."--Resource description page.
Title from resource description page (viewed February 17, 2015).
Presenter, Michael Hartl.
Keywords: Ruby (Computer program language); Web applications -- Development; Application software -- Development; Electronic books